Price and trading response to public information - Magdalena Grothe (European Central Bank (ECB), 2010)
In their seminal paper French and Roll (1986) postulate that public information affects prices before anyone can trade on it. In contrast, several models assuming heterogeneous investors show that public news releases are directly followed by high trading volume. Empirical evidence on this question is still mixed, primarily due to the lack of sufficiently precise data. This paper examines the process of price adjustment to public news in an electronic limit order market, based on very precise information from the largest European bond futures market. The results show that the price response to public news is gradual and accompanied by trading. Good (bad) news releases are followed by a sequence of positive (negative) returns and a large buying (selling) activity in the first seconds after the news release.
Keywords: E44; G14; 330; information processing; macroeconomic announcements; market microstructure; price adjustment; Informationsverhalten; Ankündigungseffekt; Marktmikrostruktur; Staatspapier; Deutschland